Hyperhomocysteinemia: The Nature of Morphological Changes in Fetal Loss (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article provides data on the results of a morphological study of the early postabortem endometrium of women with hyperhomocysteinemia in the early stages of fetal loss before 8 weeks of gestation in order to identify the causes of reproductive losses. The analysis was carried out on 26 women who received treatment with folate group drugs, who made up group 1 and 28 women without pregravidar preparation, who made up group 2.